Diagnostic approach for mediastinal masses with radiopathological correlation. Issue 162 (May 2023) - Taka, Masashi; Kobayashi, Satoshi; Mizutomi, Kaori; Inoue, Dai; Takamatsu, Shigeyuki; Gabata, Toshifumi; Matsumoto, Isao; Ikeda, Hiroko; Kobayashi, Takeshi; Minato, Hiroshi; Abo, Hitoshi
Abstract: Purpose: Mediastinal masses have various histopathological and radiological findings. Although lymphoma is the most common type of tumor, thymic epithelial and neurogenic tumors are common in adults and children, respectively, but several other types are difficult to distinguish. No previous review has simply and clearly shown how to differentiate mediastinal masses. Method: We conducted a review of the latest mediastinal classifications and mass differentiation methods, with a focus on neoplastic lesions. Both older and recent studies were searched, and imaging and histopathological findings of mediastinal masses were reviewed. Original simple-to-use differentiation flowcharts are presented. Results: Assessing localizations and internal characteristics is very important for mediastinal mass differentiation. The mass location and affected organ/tissue should be accurately assessed first, followed by more qualitative diagnosis, and optimization of the treatment strategy. In 2014, the International Thymic Malignancy Interest Group presented a new mediastinal clinical classification. In this classification, mediastinal masses are categorized into three groups according to location: prevascular (anterior)-, visceral (middle)-, and paravertebral (posterior)-compartment masses. Then, the internal characteristics and functional images are evaluated. Conclusions: Differentiation of mediastinal masses is very difficult. However, if typical imaging findings and clinical characteristics are combined, reasonable differentiation is possible. In each patient, proper differential diagnosis may contribute to better treatment selection.